Simulating the Computer Science Closed Laboratory in an Asynchronous Learning Network - Margush, Timothy (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
The quiz tool that is part of the WebCT package is used to provide an asynchronous simulation of a (synchronous) closed laboratory experience to beginner computer science students. The technique suggested in this paper and which may be applied to other disciplines, offers students a guided path through an exploratory, discovery based learning experience.